Very-high thermal and electrical conductivity in overpressure-processed Bi2Sr2CaCu2O8+x wires. (2nd May 2018) - Bonura, M; Avitabile, F; Barth, C; Jiang, J; Larbalestier, D; Fête, A; Leo, A; Bottura, L; Senatore, C
Abstract: The residual-resistivity ratio ( RRR ) of the normal-metal matrix is a key parameter for the electrical and thermal stability of technical superconductors. In Bi2 Sr2 CaCu2 O 8 + x (Bi-2212) round wires, the precursor powders are embedded in a Ag matrix without any diffusion barrier, and elemental diffusion from the superconducting filaments into the Ag might be expected to contaminate the matrix during the melt processing required for high critical current density development. This work shows that the overpressure processing, which is adopted to enhance the critical current performance, improves the thermal and electrical conductivities of the conductor, too. In the case of wires reacted with a standard processing performed in 1 bar O2, the RRR of the Ag matrix is about 90, in spite of the simple conductor design that does not include diffusion barriers. Increasing the total reaction pressure to 100 bar improves the RRR to about 200. The differences in RRR reflect on the thermal conductivity of the whole conductor, which has been investigated in magnetic fields up to 19 T.